74‐3: Multicolor 1250 ppi OLED Arrays Patterened by Photolithography. Issue 1 (May 2016) - Malinowski, Pawel E.; Ke, TungHuei; Nakamura, Atsushi; Vicca, Peter; Wuyts, Magalie; Gu, Danli; Steudel, Sören; Janssen, Dimitri; Kamochi, Yoshitaka; Koyama, Ichiro; Iwai, Yu; Heremans, Paul
Abstract : In this paper, we demonstrate multicolor OLEDs patterned sideby‐side by photolithography. 1250 ppi arrays with 10 μm subpixel pitch are shown. The chemically amplified, i‐line photoresist enables submicron pitch and aperture ratio above 60%. OLED photolithography paves the road to cost‐effective, full‐color displays with 4K and 8K resolution.